Identification of Suitable Rural Development Indicators - Rajive Gupta (Dr. Chinmay Pandya, 2022)
The objective of this paper is to identify suitable rural development indicators which are easy to compile and analyze. These indicators can also be presented at the village level depicting their current status of rural development. With increasing emphasis on local governance, Gram Panchayats will be playing a key role in the rural development process. These indicators will help the elected representatives and Panchayat officials to track their progress as well as compare the outcome of their efforts with that of other Gram Panchayats in the area of rural development. The suggested indicators have been grouped in seven broad headings such as basic data, social indicators, economic indicators, educational indicators, wellness and health indicators, access to public amenities, and natural environment indicators. These indicators will greatly help Gram Panchayats, planners, policymakers to learn and improve upon shortcomings and replicate successes achieved in rural development.